Do policy incentives affect the environmental impact of private car use? Evidence from a sample of large cities - Keiko Hirota; Jacques Poot (European Regional Science Association (ERSA), 2003)
In this paper we study the effectiveness of tax incentives and public transportation prices on the environmental impact of private motor vehicle use in OECD countries and in some non-OECD countries in Asia. We develop a model of energy consumption and CO2 emission by private motor vehicles in relation to private transportation infrastructure, public transportation prices, traffic conditions, the user cost of cars, and the income of car users. The user cost of cars is decomposed into acquisition, ownership and running cost. Each component is split into a tax/subsidy segment and a resource cost segment. Our model is estimated with data from 49 large cities, i.e. 40 from OECD countries and 9 from non-OECD countries in Asia. Structural differences in model outcomes between these two sets of countries are identified. Our results suggest that an incentive-based system that rewards higher environmental performance, such as differential tax rates by vehicle age, can be effective.
Keywords: 330